1996
DOI: 10.1111/1523-1747.ep12328197
|View full text |Cite
|
Sign up to set email alerts
|

Altered Insulin-like Growth Factor–II (IGF-II) Level and IGF-Binding Protein–3 (IGFBP-3) Protease Activity in Interstitial Fluid Taken from the Skin Lesion of Psoriasis

Abstract: In the present study, we have investigated insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) in serum and artificially raised blister fluid from uninvolved and involved areas of nine patients with psoriasis. Both levels of IGFs and IGFBP-3, and profiles of IGFBP in serum and fluid from the uninvolved areas of these patients were comparable to those seen in normal subjects. In fluid from the involved areas, the IGF-II but not IGF-I level was significantly elevated. Among five molecular form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Thus, the protease modulates IGF availability from IGFBP-3 and, in turn, modulates the activity of this protease. In skin interstitial fluid taken from psoriatic skin lesions, the IGF-II level is significantly elevated and IGFBP-3 protease activity is greatly reduced due to a locally produced, unidentified inhibitor(s) (5). In the same fluid, the PAI-1 level was significantly higher and the PAI-2 level was lower than those in skin interstitial fluid taken from the uninvolved skin (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the protease modulates IGF availability from IGFBP-3 and, in turn, modulates the activity of this protease. In skin interstitial fluid taken from psoriatic skin lesions, the IGF-II level is significantly elevated and IGFBP-3 protease activity is greatly reduced due to a locally produced, unidentified inhibitor(s) (5). In the same fluid, the PAI-1 level was significantly higher and the PAI-2 level was lower than those in skin interstitial fluid taken from the uninvolved skin (31).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we have shown IGFBP-3 protease activity in skin interstitial fluid from normal skin and uninvolved skin of psoriasis, and that such activity is inhibited in involved psoriatic skin area (4,5). IGFBP messenger ribonucleic acids are present in skin epidermis (6), and keratinocytes are capable of producing IGFBPs, including IG-FBP-2, -3, -4, and -6 and possibly IGFBP-5, with IGFBP-3 being the major form (7)(8)(9).…”
mentioning
confidence: 93%
“…However, studies utilising more physiological conditions, perhaps involving perfusion, to simulate the kinetics of clearance in the extracellular environment, will be required to provide more compelling evidence. In this respect, comparatively little is known about tissue clearance and pericellular concentrations of IGFBPs, although there are some reports (Xu et al, 1996, Xu et al, 1997. The secretion of IGFBPs into the extracellular environment might also serve as a barrier to limit access of IGFs to cellular receptors, and such a proposal has been made for the mammary gland for IGFBP-4 (Allar and Wood, 2004) and IGFBP-5 (Flint et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of such an inhibitor(s) in serum does not preclude that it could be produced and function out of the bloodstream, i.e., in the vicinity of a tumor by interacting with tissue-produced IGFBP-3 proteases, e.g., by tumor stromal cells. This has been reported to occur in interstitial fluid taken from psoriatic skin lesions (Xu et al, 1996). Our knowledge of where IGFBP-3 proteases are produced and how they are regulated, however, remains limited.…”
Section: Discussionmentioning
confidence: 99%